2017
DOI: 10.1021/jacs.7b02027
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium/Silver Synergistic Catalysis in Highly Enantioselective Cycloisomerization/Cross Coupling of Keto-Vinylidenecyclopropanes with Terminal Alkynes

Abstract: A rhodium/silver synergistic catalysis has been established, enabling cycloisomerization/cross coupling of keto-vinylidenecyclopropanes (VDCPs) with terminal alkynes toward the regio- and enantioselective formation of diversified tetrahydropyridin-3-ol tethered 1,4-enynes in good yields and high ee values. In this synergistic catalysis, Rh(I) and Ag(I) catalysts selectively activate keto-VDCP substrates and terminal alkynes to generate the π-allyl Rh(III) complex of oxa-rhodacyclic intermediate and Ag alkynyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 165 publications
0
20
0
Order By: Relevance
“…2,3 3-substituted piperidine derivatives are at the core of many potent therapeutic agents (Figure 1), 2,4,5 and methods for their preparation have attracted growing attention. 6 However, asymmetric syntheses of 3-substituted piperidines via direct functionalization of racemic substrates are scarce. 7 Figure 1.…”
mentioning
confidence: 99%
“…2,3 3-substituted piperidine derivatives are at the core of many potent therapeutic agents (Figure 1), 2,4,5 and methods for their preparation have attracted growing attention. 6 However, asymmetric syntheses of 3-substituted piperidines via direct functionalization of racemic substrates are scarce. 7 Figure 1.…”
mentioning
confidence: 99%
“…The kinetic isotope effect of this reaction was measured on the basis of parallel experiments, and a k H / k D value of 5.7 was obtained (Scheme 3, a), which suggests that the C−H activation might be involved in the turnover‐limiting process. Upon treatment of 3 a with 2 a in the presence of treated [RhCp*(MeCN) 3 ][SbF 6 ] 2 (silver content was measured by ICP‐OES, [15] see Supporting Information at page S8) and PivOH in TFE:DCE (1:1) at 80 °C, the product 4 a could be accessed in 81% yield, indicating that Cp*RhX 2 complex [16] is the active catalyst (Scheme 3, b). Treatment of 1 a with AgSbF 6 in TFE:DCE (1:1) for 3 hours produced 3 a in 85% yield; heating compound 1 a without AgSbF 6 for 12 hours afforded 3 a only in 18% yield after 12 h. These results suggested that Ag(I) played an important role in the formation of cyliczed isoquinoline product 3 a and the active Cp*RhX 2 complex (Scheme 3, c).…”
Section: Figurementioning
confidence: 99%
“…A-BODIPY has the ability to recognize Hg 2+ and Ag + . It is presumed that the terminal alkynyl group can react with Ag + to generate heavy metal acetylide [39], and react with Hg 2+ to undergo hydroxy-mercury reaction, which can be obtained by 1 H NMR and MS analysis (Figure S20). Undoubtedly, this reflects the controllability of the sensor recognition site.…”
Section: Detection Mechanismmentioning
confidence: 99%